anonymous
  • anonymous
WILL MEDAL AND FAN! PLEASE, THIS IS URGENT! Solve √(k-7) = √(k) -1 for k.
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
katieb
  • katieb
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
Nnesha
  • Nnesha
take square both sides to cancel out square root
anonymous
  • anonymous
i tried that and i got this \[k-7= k-1\]
anonymous
  • anonymous
or is it k+1? i think its K-1

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

anonymous
  • anonymous
can anyone help me please?
freckles
  • freckles
\[\sqrt{k-7}=\sqrt{k}-1 ?\]
anonymous
  • anonymous
I'm trying to have it done by the time my best friend gets on.
anonymous
  • anonymous
yep!
anonymous
  • anonymous
the choices are: 20 16 4 8
Nnesha
  • Nnesha
oh nvm I didn't notice the parentheses
freckles
  • freckles
square both sides
freckles
  • freckles
you will need this on the right hand side \[(a-b)^2=a^2+b^2-2ab\]
anonymous
  • anonymous
\[\sqrt{k-7} = \sqrt{k} -1\]
freckles
  • freckles
have you expanded the right hand side yet?
anonymous
  • anonymous
i dont know what that means
anonymous
  • anonymous
i got to this point\[k-7 = k-1\]
freckles
  • freckles
\[\sqrt{k-7}=\sqrt{k}-1 \\ \text{ Square both sides } (\sqrt{k-7})^2=(\sqrt{k}-1)^2 \\ k-7=(\sqrt{k}-1)^2\] recall \[(a-b)^2=a^2+b^2-2ab\] you can use this to expand the square part on the right hand side
anonymous
  • anonymous
ooooohhhhhhh soooooo\[k+1-2k\]
anonymous
  • anonymous
right? so \[k+1-2k=k-7\]
freckles
  • freckles
close
freckles
  • freckles
you had a sqrt( ) on k
freckles
  • freckles
\[(a-b)^2=a^2+b^2-2ab \\ (\sqrt{k}-1)^2=(\sqrt{k})^2 +(1)^2-2(\sqrt{k})(1) \\ (\sqrt{k}-1)^2=k+1-2 \sqrt{k}\]
anonymous
  • anonymous
oh right. \[k-7 = k+1 - 2\sqrt{k}\]
freckles
  • freckles
so you really have \[k-7=k+1-2 \sqrt{k} \text{ or subtracting } k \text{ on both sides } -7=1-2 \sqrt{k}\]
freckles
  • freckles
isolate the sqrt(k) part
anonymous
  • anonymous
k\[-2\sqrt{k}=-8\]
anonymous
  • anonymous
right?
freckles
  • freckles
yeah
freckles
  • freckles
divide both sides by -2
anonymous
  • anonymous
\[\sqrt{k}=4\]
anonymous
  • anonymous
k=16!
freckles
  • freckles
yep and you can check that by pluggin it in
anonymous
  • anonymous
THANK YOUUU soooooooooo muchhh
anonymous
  • anonymous
Im a fan a medals
freckles
  • freckles
\[\sqrt{k-7}=\sqrt{k}-1 \\ k=16 \\ \sqrt{16-7}=\sqrt{9}=3 \\ \text{ and the other side } \sqrt{16}-1=4-1=3 \] 3=3 k=16 is definitely a solution since it gives a true equation when pluggin it back in
anonymous
  • anonymous
thank youuu
freckles
  • freckles
np

Looking for something else?

Not the answer you are looking for? Search for more explanations.